A carnavalização do século XVI: uma análise do riso em François Rabelais - Sacramento, Jefferson Nery (2023)
This study presents a critical analysis of the historical and anthropological phenomenon of laughter in two works, Pantagruel (1532) and Gargantua (1534), written by the celebrated literary figure of popular culture, François Rabelais (1483?-1553). Rabelais became known as a writer for his entertaining style in French Literature History in the sixteenth century, a period marked by constant attacks on ideas in the historical context of the European Renaissance. By revisiting the context of laughter, this study explains the importance of Rabelais carnivalesque literature and also demonstrates how the author used humorous elements in his fiction to comment on society, politics, religion, and culture of the historical context in which he lived. As a result, this investigation contributes to a more current historical reflection on the relationship between laughter and humanity, with Rabelais books as a source.